Lactase insufficiency: a modern concept of nutrition - S. V. Belmer (Лечащий Врач)
Lactase insufficiency is widespread throughout the world. The development of clinical symptoms in lactase deficiency is due to the metabolism of lactose, which is not broken down in the small intestine and processed mainly by colon microorganisms with the formation of short-chain fatty acids and gases, leading to the development of diarrhea, flatulence, and often pain. Making a preliminary diagnosis based on complaints and the clinical picture is relatively simple, but a lot of methods have been developed to confirm the final diagnosis. These include, in particular, a glycemic test with a lactose load and a breath test with the determination of hydrogen in exhaled air after a lactose load. It is also possible to study the activity of lactase in biopsies of the mucous membrane of the small intestine and genetic research. Also in outpatient pediatric practice, the determination of carbohydrates in feces is used. This analysis is not specific, but can help in the diagnosis of carbohydrate malabsorption syndrome, especially in children in the first months of life. The general concept of nutrition in lactase insufficiency includes limiting lactose in the diet by eliminating lactose-containing foods or prescribing enzyme (lactase) replacement therapy. However, the degree of restriction depends on the degree of lactose intolerance and lactose can remain in the diet in tolerable amounts. A dairy-free diet is not recommended because milk is an important source of nutrients necessary for growth and metabolism, especially in childhood. The importance of milk in this regard is preserved in adults. Most individuals with lactase insufficiency can tolerate lactose-reduced fermented milk products. The use of probiotics helps to reduce the clinical symptoms of lactase insufficiency. It is also possible to use industrial lactose-free dairy products. It is important to correct a possible deficiency of minerals and vitamins in conditions of restriction of dairy products in the diet.